Influencia de la temperatura de revenido en la tenacidad a la fractura del acero ASTM A-36, entre 500 a 650ºC - Solís Ulloa, William Fernando (2017)
In this research has been carried a study about the influence of tempering temperature on the fracture toughness of the steel ASTM A-36, in the range from 500 to 650 °C, for a tempering time of 45 minutes. In the regimen elastoplastic integral on applying the analysis based on the mechanics to the fracture elastoplastic. For the study were employed three points bend specimen type SENB (Single Edge Notched Bend), with a wide approximate one of W = 25 mm, and thickness of (B = W/2), according to the norm ASTM E-1820, which were submitted to a state quenching in water (840ºC), and the state of tempering by 500, 550, 600 and 650 °C to a time of 45 minutes. Subsequently the specimens were cracked with a machine of fatigue of flexion in three points until reaching the relation from a/w approximately to 0,6. The cracked by fatigue was carried out with a relation . For the determination of the curves , itself employment the method from a single specimen test. which permits to determine a curve complete to testing so alone a specimen, being the indirect method of the elastic compliance technique employed for the determination of the size of the crack. The rehearsals of the Fracture Toughness show that the increased the tempering time at a temperature of 650º C, the parameter was determined in the start of the stable growth of the crack.. And the values obtained were 32.34, 44.84, 57.25, and 73.24 KJ/m2 in quenching state by 500, 550, 600 and 650°C respectively for 45 minutes. Of the obtained results concluding that the increases tempering time, the fracture toughness increases.